Dubinin's theory and its contribution to adsorption science - Stoeckli, Fritz (My University, 2001)
Dubinin's theory for the volume filling of micropores (TVFM), originally developed for the adsorption of single vapours by microporous solids such as activated carbons and Zeolites, has gradually been extended to other areas. They include immersion calorimetry, the adsorption of water vapour and of mixtures, as well as adsorption front aqueous solutions. Recent studies in the field of adsorption from aqueous solutions, by activated carbons, suggest that the principle of temperature invariance is fulfilled and in the case of phenolic compounds a modified DRK equation can be used to predict the adsorption equilibrium over a certain range of temperatures. Computer modelling of CO2 adsorption by carbons at 273 K leads to micropore distributions, which are in good agreement with those derived from other techniques. It also appears that the model isotherm, in single slit-shaped micropores can be fitted to the Hill-de Boer isotherm, in agreement with mathematical studies of the origin of the Dubinin-Astakhov equation.
Keywords: adsorption; microporosity; immersion calorimetry; activated carbons; simulation; ACTIVE-CARBON BEDS; MICROPOROUS CARBONS; ASTAKHOV EQUATION; RADUSHKEVICH-EQUATION; DYNAMIC ADSORPTION; BINARY ADSORPTION; AQUEOUS-SOLUTIONS; VAPOR ADSORPTION; MYERS-PRAUSNITZ; ADSORBENTS